A Transformative Learning Model Towards a Peaceful Death Preparation through Buddhist Peaceful Means for Thai Buddhist Adults - Chiewchalalai, Charuwan; (Hansa Dhammahaso), Phrakhupalad Pannavoravat; Khunakaro, Phramaha Somphong; Dhammavaro, Phra Theerasak (Journal of International Buddhist Studies, 2023)
No one indeed escapes death. To acquire valuable knowledge and enhance a peaceful death for a decent quality of life, it is essential to comprehend the quality of death and dying. Regarding this, it is crucial to prepare for a peaceful death through transformative learning. Therefore, this research aims to 1) study the concept of dying and peaceful death in general understanding and Theravāda Buddhist Teachings; 2) explore the theory of transformative learning; and 3) propose a model as a guideline to support peaceful death preparation. Data were compiled through documentary analysis, synthesis, and in-depth interviews with about twenty key informants split into five groups, using a qualitative research methodology. Based on the research objectives, the results were separated into three main categories and revealed that individuals desire both a decent life and a peaceful death. Knowledge and attitudes about death can have a significant impact on a person’s way of life. Whereas in Buddhism, the five aggregates dissolve upon death and are significantly influenced by Kamma, non-self, impermanence, and suffering. Constantly contemplating death liberates an individual from attachment to both pleasant and unpleasant and enables one to confront death intelligently and peacefully. To enable peaceful death preparation in the cultural context of Thai Buddhism, the research contributes to the PSIAM model, which specifies the crucial elements and processes of transformative learning. This model offers Thai Buddhist adults an invaluable framework for comprehending and encouraging peaceful death preparation practices, and it may have implications for other cultural and religious contexts.